ACID ACTIVATION OF PRRENJAS CLAY MINERAL - Altin Mele; Krenaida Taraj; Arjan Korpa (Journal of Engineering & Processing Management, 2015)
Prrenjas clay mineral is found in southeast Albania and has a high content on bentonite. Theinfluence of the sulphuric acid activation on the composition, structure and surface properties ofPrrenjas clay mineral is investigated in this study by means of elemental chemical analysis, X-Ray Diffractometry, IR Spectroscopy and gas adsorption-desorption measurement. H2SO4concentrations of 0.143 M, 0.232 M, 0.371 M, 0.537 M, 0.734 M, 0.927 M and 1.456 M were used inthe treatment of samples. The treatment by increasing the acid concentration brings the leaching ofAl3+, Fe2+, Mg2+ from the clay structure. The specific surface area and the pore volume of the claysamples increases respectively from 83 m2/g and 0.069 cm3/g for the untreated clay to 420 m2/g and0.384 cm3/g for the clay mineral treated with 1.456 M H2SO4 solution. New mesopores were createdduring the acid activation mainly in the range of 2 - 8 nm. For the samples treated with 0.927 Mand 1.456 M solutions the increase in specific surface area and pore volume is very high. Thecationic exchange capacity decreases steadily with the concentration of H2SO4 used for thetreatment.
Keywords: clay mineral; acid activation; surface properties